Disruptive technologies for hemodialysis: medium and high cutoff membranes. Is the future now? - Reis,Thiago (2021)
Abstract In the past decade, a new class of hemodialysis (HD) membranes (high retention onset class) became available for clinical use. The high cutoff (HCO) and the medium cutoff (MCO) membranes have wider pores and more uniformity in pore size, allowing an increased clearance of uremic toxins. Owing to the mechanism of backfiltration/internal filtration, middle molecules are dragged by the convective forces, and no substitution solution is needed. The HCO dialyzer is applied in septic patients with acute kidney injury requiring continuous kidney replacement therapy. The immune response is modulated thanks to the removal of inflammatory mediators. Another current application for the HCO dialyzer is in hematology, for patients on HD secondary to myeloma-kidney, since free light chains are more efficiently removed with the HCO membrane, reducing their deleterious effect on the renal tubules. In its turn, the MCO dialyzer is used for maintenance HD patients. A myriad of clinical trials published in the last three years consistently demonstrates the ability of this membrane to remove uremic toxins more efficiently than the high-flux membrane, an evolutionary disruption in the HD standard of care. Safety concerns regarding albumin loss as well as blood contamination from pyrogens in the dialysate have been overcome. In this update article, we explore the rise of new dialysis membranes in the light of the scientific evidence that supports their use in clinical practice.